Developing supplementary English reading materials for Vocational High School - Hanswaty Noho; Hasanuddin Fatsah; Rasuna Talib (International Journal of Humanities and Innovation (IJHI), 2018)
The main problem of this study was “What are students of the Vocational School of Computer Networks need in learning English?” and “How is the development of supplementary English materials for reading skill?” The objective aimed at describing the development of supplementary reading materials for the tenth-grade vocational school based on the 2013 curriculum. The subject was the computer networks students in grade tenth in the 2015/2016 academic year consisting of twenty-two students (five males and 17 females). This research used R & D (Research and Development) method. The data were gathered from a number of sources, including students’ need analysis of English reading materials in grade X in the students’ book of 2013 curriculum, supplementary development of the English reading materials for computer networks students, and expert validation of supplementary English reading materials and students’ response after used the supplementary English materials. The findings showed that more than 30% of students were difficult to read the computer networks text and to understand the meaning of the text. The result of students’ book analysis was none of the reading materials appropriate for computer networks department, mostly provided General English. In developing the supplementary English reading materials for computer networks students, there were four stands, in which the current research only applied three out of the four stands, including define, design and developed. This supplementary English reading material helped the computer networks students to learn English based on their need.